2014
DOI: 10.1016/j.fertnstert.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Live birth from a 46-year-old using fresh autologous oocytes through in vitro fertilization☆

Abstract: The prognosis for a live birth from IVF in a patient with very advanced reproductive age, particularly with an undetectable AMH level using autologous oocytes, remains extremely poor. This case should be interpreted with caution so as to not provide false hope to women aged 45 and above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Few of the earlier case studies suggest that IVF treatment should be limited to patients <43 years of age (9), because a reasonable chance for success with homologous oocytes is observed up until the end of the 44th year (10). Limited reports of live births are available in older women from autologous oocytes after IVF-ET (11)(12)(13). The present report discusses the case of a 50-year-old woman who delivered a healthy baby after IVF with her own oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the earlier case studies suggest that IVF treatment should be limited to patients <43 years of age (9), because a reasonable chance for success with homologous oocytes is observed up until the end of the 44th year (10). Limited reports of live births are available in older women from autologous oocytes after IVF-ET (11)(12)(13). The present report discusses the case of a 50-year-old woman who delivered a healthy baby after IVF with her own oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…One study of a series of 288 women aged 45 or over to use autologous oocytes demonstrated only livebirth success in women no older than 45 and who produced at least five oocytes [9]. The oldest age at livebirth previously reported was 46 years [14], but from a fresh cycle where 7 oocytes collected and four embryos transferred.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that reports of pregnancies in women of advanced reproductive age using autologous oocytes have recently appeared [7][8][9]. Many would argue that the ages reported would previously have been considered Bfutile.F ertility treatment success rates are rising every year, and it is possible that treatment that was previously considered futile may simply represent another poor prognosis situation.…”
Section: Commentmentioning
confidence: 99%
“…While reports of patients conceiving late in life with their own oocytes have recently appeared [8][9][10], elevated FSH levels in women over 40 appear to have a high negative predictive value in estimating subsequent live birth with the patient's own oocytes [11][12][13][14]. In our clinic, women over the age of 40 with menstrual day 3 FSH levels above 20 mIU/mL are advised to repeat the test, but if the results are consistently high, they are offered immediate oocyte donation due to the significant improvement in success rates (>50%) that can be expected compared to using autologous oocytes [15].…”
Section: Introductionmentioning
confidence: 99%